PREREQUISITES OF ARMED AGGRESSION BY THE RUSSIAN FEDERATION AGAINST UKRAINE: FROM HYBRID OPPOSITION TO LARGE-SCALE ARMED INVASION - Vashchenko, Ihor; Stadnyk, Anatoliy; Poltavskyi, Eduard (Honor and Law, 2023)
The article examines the views of domestic and foreign scientists on the peculiarities of the development of the modern world political process, the development of the global information space and technologies, the specifics of the social, economic and political conditions of the development of the modern world community that influenced the nature and peculiarities of the conduct of modern wars; analyzed the attempt to transition to force principles in relations between states, which was the beginning of the crisis of the European security system; formulated a vision of the concept of hybrid war through the prism of Ukrainian-Russian relations, as a kind of reference point in conflicts of a new type, state-legal mechanisms for ensuring the national security of Ukraine, justified the understanding of the essence of hybrid war as a new form of global confrontation in international relations, where hybrid war has become a new as a means of conducting an armed struggle at the beginning of the 21st century ‒ as the desire of one country to impose its political will on another through a complex of measures of a political, economic, informational and actually military nature ‒ without declaring war in accordance with the norms of international law; the main components of a hybrid war are characterized, with the help of which simultaneous influence on the opponent is carried out in various directions, where the determining components are informational, ideological, psychological, economic, political, diplomatic, military, technological, resource, energy; approaches are systematized understanding of the confrontation between Ukraine and the Russian Federation after 1991, namely the establishment of specific mass psychological attitudes, which at the time of transition of the conflict to the phase of large-scale armed aggression, were used to weaken Ukrainian statehood. An analysis was carried out to determine the location of the hybrid war as a prerequisite for the armed aggression of the Russian Federation against Ukraine. So, hybrid war is a new type of conflict that will be constantly encountered in the world in the last decades practice, therefore the world community must learn to adequately respond to such challenges and learn to effectively confront these threats.